EnglishMEASURING CONSUMER REACTIONS TO AUGMENTED REALITY IN THE FITTING PROCESS IN BUYING ACCESSORIES USING IN-DEPTH INTERVIEW CASE STUDY OF INTERAXE.ID - Shabira Shafa Afra; Budi Permadi Iskandar (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Since all businesses have to improve their marketing digitally, as well as increase customer interactions, it takes a platform that is widely accessed by all people during this digitalization era, namely social media. In this digitalization era, most people browse online shop catalogs especially in the fashion industry through Instagram and e-commerce social media. Therefore, Instagram can be said as the main marketing platform that has to present product visualization. Not only provide portfolios and catalogs that can be accessed publicly, but the company can also design various marketing content to increase the audience’s knowledge about the products as well as the digitalization itself. INTERAXE.ID came up with a relatively new innovation with Instagram platform as their entry market, where the company had to increase the audiences’ awareness and familiarity which will lead to costumer’s acceptance and gaining early adopters. Keywords: INTERAXE.ID; Marketing Strategy; Social Media; Instagram; Costumer’s Acceptance; Early Adopters